Associations of aldehyde exposure with serum uric acid and hyperuricemia among U.S. adults from NHANES 2013–2014 - Jinyue Li; Hanping Ma; Jingyang Wang; Han Ma (Heliyon)
Background: Aldehyde is a kind of important environmental pollutant, which has been demonstrated to be associated with increased risks of various chronic diseases with the economic and social development. However, the effects of aldehydes on serum uric acid (SUA) and hyperuricemia remained inexplicit, and the potential mediating pathways for this relationship needed to be addressed. Methods: This study investigated the associations of individual and mixed aldehydes with SUA and hyperuricemia among 1588 U S. adults from the National Health and Nutrition Examination Survey 2013–2014. The generalized linear regression model was applied to assess the effects of individual aldehydes and the Bayesian kernel machine regression were incorporated to examine the impacts of mixed aldehydes. Mediation analyses were performed to explore the roles of inflammation and oxidative stress indices in aldehyde-induced SUA and hyperuricemia. Moreover, we conducted subgroup analyses for demographic and physical factors to detect disparity between groups. Results: Propanaldehyde, butyraldehyde, and hexanaldehyde were associated with higher SUA level and butyraldehyde was correlated with increased hyperuricemia prevalence after multiple correction. Positive relationships between aldehyde mixtures and SUA level were also observed and hexanaldehyde contributed most. In addition, lymphocyte count and gamma glutamyl transferase partially mediated the associations between propanaldehyde, butyraldehyde, hexanaldehyde and SUA level, with mediation proportions ranging from 19.105 % to 27.316 %. Subgroup analyses showed that SUA level of participants with obesity, hypercholesterolemia, and hypertension tended to be more sensitive to aldehyde exposure. Conclusions: Our results highlighted that multiple aldehydes mixtures exposure might increase SUA level, and revealed underlying mediating role of inflammation and oxidative stress. These findings provided crucial evidence for the impacts of environmental pollutants on human health and further prospective studies are still required to verify the findings.